Transforming Water Hyacinth into a Community Asset: CSR-Based Participatory Innovation in Cengklik Reservoir, Indonesia - Dewangga Cipta M.; Siti Fatonah; Shoiful Amri (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2025)
The rapid proliferation of water hyacinth (Eichhornia crassipes) in Cengklik Reservoir, Boyolali, has caused acute problems for water quality, the aquatic ecosystem, and local economic activities. Through the CSR initiative Masyarakat Sobokerto Peduli Waduk Cengklik (Sobokerto Community Cares for Cengklik Reservoir), initiated by PT Pertamina Patra Niaga AFT Adi Sumarmo since 2021, this invasive species is no longer seen as a nuisance but is being leveraged as a productive resource. This study employs a Participatory Action Research (PAR) approach to investigate, support, and assess collective management of water hyacinth by converting it into various products among the assisted community group between 2022 and 2025. The findings demonstrate the transformation of water hyacinth into a range of eco-friendly products: (1) liquid and solid organic fertilizers with NPK levels that meet laboratory criteria, (2) biogas via household-scale anaerobic digesters further developed as a renewable electricity source (Lisendo) for public street lighting, (3) organic fish feed with local formulations that strengthen aquaculture group food security, (4) silage as alternative goat feed with fermentative nutrients, and (5) eco-enzymes for improving reservoir water quality. Each year, there has been measurable progress in both technology adoption and the number of engaged groups, indicating expanded community capacity to manage local resources sustainably. These results affirm that integrating CSR, technological innovation, and grassroots participation can convert invasive weeds into strategic ecological, economic, and social assets.